The Essence of Modern Technology to Handle Passengers in Poland In the Opinion of the Young Respondents - Grażyna ROSA (Communications of International Proceedings, 2021)
The article aims to demonstrate how much modern technologies applied to shape the offering of transport providers are important for traveller service, what is the price of such technologies and how can they be applied. The achieve this aim, critical analysis was carried out of the available results of secondary research and primary research was done in the form of a survey by means of a questionnaire. Own studies into modern technologies applied to handle passengers in Poland in the context of their importance and possible applications were conducted on a representative sample of 331 young travellers. The research was carried out from October 2017 to March 2018 on a random sample of 350 people from all over Poland, meeting the age requirement and thus constituting a homogeneous sample of “young adults” aged 18-29 years The results showed that the evaluation of rail passenger transport and public road transport improved as the respondent placed more emphasis on modern technologies. Detailed results indicated the following aspects as the most important for the respondents: possibility to check connections on the Internet, possibility to buy a ticket on the Internet or with a mobile device and the possibility to have a ticket in electronic form.
Keywords: Passenger Service; Modern Technologies.